Platelet-Rich Plasma Versus Bone Marrow Aspirate Concentrate for Hip Disorders: A Narrative Review of Biological Rationale, Clinical Evidence, and Research Priorities - Se Yeong Jeon; Chul Hee Jung; Seok-Yeon Choi; Dong Ha Lee (Bioengineering, 2026)
Hip disorders—including hip osteoarthritis (OA), greater trochanteric pain syndrome (GTPS) with gluteal tendinopathy, femoroacetabular impingement syndrome (FAIS) with associated labral pathology, and osteonecrosis of the femoral head (ONFH)—are common causes of pain and functional loss, and several are refractory to conventional non-operative care. Platelet-rich plasma (PRP) and bone marrow aspirate concentrate (BMAC) are the two most widely used autologous orthobiologics, yet a comparative appraisal of these agents across the full spectrum of hip pathology is lacking. This narrative review is based on structured searches of MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and Scopus for clinical studies—randomized controlled trials (RCTs), comparative studies, and prospective series—and evidence syntheses evaluating PRP or BMAC in hip disorders; studies were synthesized narratively by biologic type and by disorder, and no formal systematic-review or scoping-review reporting protocol was applied. Society guidelines and consensus documents were additionally examined, and PRP formulation subgroups (leukocyte-rich [LR-PRP] versus leukocyte-poor [LP-PRP]) were considered, including a numerically larger, but methodologically heterogeneous and comparator-sensitive evidence base for hip disorders, supported by several RCTs and pooled analyses in hip OA and in gluteal tendinopathy; however, findings are heterogeneous, effect sizes are modest, a network meta-analysis found intra-articular saline to be statistically indistinguishable from PRP for hip OA pain, and the only adequately powered placebo-controlled RCT in GTPS was negative. BMAC evidence in the hip is concentrated almost entirely in surgical augmentation of core decompression for ONFH, where results are stage-dependent and include a negative double-blind RCT in post-collapse disease; intra-articular BMAC for hip OA rests on small uncontrolled cohorts, and no standalone hip BMAC RCT has been published. No RCT directly compares PRP with BMAC for any hip disorder; the closest evidence is a knee OA meta-analysis, in which both biologics outperformed hyaluronic acid with no clear separation between the two. Current society guidance advises strongly against PRP for hip OA, and no guideline currently incorporates BMAC for hip indications. Neither biologic is established as superior. The search for standardized, hip-specific, adequately powered head-to-head RCTs incorporating biologic characterization, structural (imaging) endpoints, and longer follow-up, represents the most important research priority in this field.